Avelumab, an anti-PD-L1 antibody, in patients with locally advanced or metastatic breast cancer: a phase 1b JAVELIN Solid Tumor study - Dirix, Luc Y; Takacs, Istvan; Jerusalem, Guy; Nikolinakos, Petros; Arkenau, Hendrik-Tobias; Forero-Torres, Andres; Boccia, Ralph; Lippman, Marc E; Somer, Robert; Smakal, Martin; Emens, Leisha A; Hrinczenko, Borys; et al. (Breast cancer research and treatment, 2018)
PURPOSE: Agents targeting programmed death receptor 1 (PD-1) or its ligand (PD-L1) have shown antitumor activity in the treatment of metastatic breast cancer (MBC). The aim of this study was to assess the activity of avelumab, a PD-L1 inhibitor, in patients with MBC. METHODS: In a phase 1 trial (JAVELIN Solid Tumor; NCT01772004), patients with MBC refractory to or progressing after standard-of-care therapy received avelumab intravenously 10 mg/kg every 2 weeks. Tumors were assessed every 6 weeks by RECIST v1.1. Adverse events (AEs) were graded by NCI-CTCAE v4.0. Membrane PD-L1 expression was assessed by immunohistochemistry (Dako PD-L1 IHC 73-10 pharmDx). RESULTS: A total of 168 patients with MBC, including 58 patients with triple-negative breast cancer (TNBC), were treated with avelumab for 2-50 weeks and followed for 6-15 months. Patients were heavily pretreated with a median of three prior therapies for metastatic or locally advanced disease. Grade ≥ 3 treatment-related AEs occurred in 13.7% of patients, including two treatment-related deaths. The confirmed objective response rate (ORR) was 3.0% overall (one complete response and four partial responses) and 5.2% in patients with TNBC. A trend toward a higher ORR was seen in patients with PD-L1+ versus PD-L1- tumor-associated immune cells in the overall population (16.7% vs. 1.6%) and in the TNBC subgroup (22.2% vs. 2.6%). CONCLUSION: Avelumab showed an acceptable safety profile and clinical activity in a subset of patients with MBC. PD-L1 expression in tumor-associated immune cells may be associated with a higher probability of clinical response to avelumab in MBC.
Keywords: B7-H1 Antigen; senioři; metastázy nádorů; Metastatic breast cancer; triple-negativní karcinom prsu; Avelumab; PD-L1; antigeny CD274; regulace genové exprese u nádorů; Triple Negative Breast Neoplasms; monoklonální protilátky; Middle Aged; Second-line; Antibodies, Monoclonal; Neoplasm Recurrence, Local; Adult; lokální recidiva nádoru; Triple-negative breast cancer; Neoplasm Metastasis; Disease-Free Survival; ženské pohlaví; protilátky anti-idiotypické; Humans; Gene Expression Regulation, Neoplastic; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; Antibodies, Anti-Idiotypic; lidé středního věku; dospělí; Female; Aged; přežití bez známek nemoci; lidé